Exchange Rate Regimes of CEE Countries on the Way to the EMU : Nominal Convergence, Real Convergence and Optimum Currency Area Criteria - Vladimir Lavrač; Tina Zumer (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
Central and Eastern European (CEE) countries are expected to join the European monetary union (EMU) in a couple of years after their accession to the EU. According to the official views of the European Commission and the European central bank (ECB), monetary integration of CEE countries in the euro area should be a multilateral, successive and phased process, leading finally to their adoption of the euro. The paper starts from the description of alternative exchange rate regimes currently in use in Central and Eastern European EU candidate countries. Their present exchange rate arrangements differ substantially, as they cover the whole spectrum of possible solutions, from currency boards to floating exchange rate regimes. By now it is known that these countries will first enter the EU and the ERM 2 (exchange rate mechanism, devised for the so-called pre-in countries, as a preparatory stage before their EMU membership), and only a few years later join the EMU and adopt the euro. The paper therefore tries to evaluate present arrangements of the candidate countries from the point of view of how compatible these arrangements are with the future ERM 2 and EMU requirements. The paper addresses some issues which are still open in the process of inclusion of CEE countries in the EMU. First, what are the interests of both parties involved (CEE countries and the EU side) regarding the dynamics of the accession of CEE countries to the EMU, and related to this, what is its likely scenario (early or late inclusion in the EMU), taking into account the balance of powers between the two sides. Second, the paper discusses the criteria for measuring readiness of individual CEE countries for joining the EMU. The analysis is focused on the debate on nominal convergence (represented by the famous maastricht convergence criteria) versus real convergence (catching up in economic development). In short, the discussion concentrates on the question whether monetary integration is possible and desirable among countries at a different level of economic development. Finally, special attention is paid to optimum currency area criteria, not only as a theoretical background for monetary integration, but also as an additional insight into the measurement of relative suitability and readiness of individual candidate countries for joining the EMU. As an illustration, the paper attempts to measure some of the optimum currency area indicators for the case of Slovenia, and finds out that Slovenia is relatively quite suitable for joining monetary integration and relatively well prepared for joining the euro area. In particular, Slovenia is not expected to be exposed to serious asymmetric shocks, once Slovenia joins the EMU.
Keywords: F02; E0; 330; Exchange Rate Regimes for CEEC; Optimum Currency Areas; Slovenia; Wechselkurssystem; Wechselkurspolitik; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Entwicklungskonvergenz; Optimaler Währungsraum; Slowenien; Osteuropa